Towards the spatial resolution of metalloprotein charge states by detailed modeling of XFEL crystallographic diffraction. Issue 2 (10th February 2020) - Sauter, Nicholas K.; Kern, Jan; Yano, Junko; Holton, James M.
Abstract : Electronic configurations at distinct metal centers within a metalloprotein may be characterized by inspecting the scattering factors at the X‐ray absorption edge. Such experiments may be feasible at XFEL sources, using Bayesian data analysis. Abstract : Oxidation states of individual metal atoms within a metalloprotein can be assigned by examining X‐ray absorption edges, which shift to higher energy for progressively more positive valence numbers. Indeed, X‐ray crystallography is well suited for such a measurement, owing to its ability to spatially resolve the scattering contributions of individual metal atoms that have distinct electronic environments contributing to protein function. However, as the magnitude of the shift is quite small, about +2 eV per valence state for iron, it has only been possible to measure the effect when performed with monochromated X‐ray sources at synchrotron facilities with energy resolutions in the range 2–3 × 10 −4 (Δ E / E ). This paper tests whether X‐ray free‐electron laser (XFEL) pulses, which have a broader bandpass (Δ E / E = 3 × 10 −3 ) when used without a monochromator, might also be useful for such studies. The program nanoBragg is used to simulate serial femtosecond crystallography (SFX) diffraction images with sufficient granularity to model the XFEL spectrum, the crystal mosaicity and the wavelength‐dependent anomalous scattering factors contributed by two differently charged iron centers in the 110‐amino‐acid protein, ferredoxin. Bayesian methods are then used to deduce, from the simulated data, the most likely X‐ray absorption curves for each metal atom in the protein, which agree well with the curves chosen for the simulation. The data analysis relies critically on the ability to measure the incident spectrum for each pulse, and also on the nanoBragg simulator to predict the size, shape and intensity profile of Bragg spots based on an underlying physical model that includes the absorption curves, which are then modified to produce the best agreement with the simulated data. This inference methodology potentially enables the use of SFX diffraction for the study of metalloenzyme mechanisms and, in general, offers a more detailed approach to Bragg spot data reduction.